Determination of Hydrochlorothiazide by Using its Quenching Effect on the Fluorescence of Bisoprolol Fumarate in Pharmaceutical Tablet Dosage Form by Indirect Spectrofluorimetry - Patel Vandana, B.; Rajanikantha, Sahu; Patel Bhumika, M. (Asian Journal of Chemistry, 2010)
A rapid, precise, accurate and specific spectroflourimetric method was developed for the determination of hydrochlorothiazide from its pharmaceutical dosage forms. The method is based on quenching of the fluorescence of bisoprolol fumarate by hydrochlorothiazide. The fluorescence intensity of mixture of bisoprolol fumarate (in optimal concentration) and hydrochlorothiazide solution was measured at 298 nm using an excitation wavelength of 229 nm and the linearity range was found to be 2-20 μg/mL. The method was validated in terms of accuracy and precision. The result of study showed that the proposed spectroflourimetric method is useful for the routine determination of hydrochlorothiazide in pharmaceutical tablet dosage form.